Evaluating the Hamstring-to-Quadriceps Rate of Torque Development Ratio as an Indicator of Knee Stability in Male Basketball Players: A Cross-Sectional Study - Maha Moore; Amin Kordi Yoosefinejad; Farzaneh Yazdani; Samaneh Ebrahimi (Shiraz University of Medical Sciences, 2024)
Background:Due to the crucial nature of knee joint stability in basketball players and the possible role of the rate of torque development hamstrings to quadriceps ratio for determining knee joint stability in the early phase of explosive movements, the purpose of this cross-sectional study was to explore the relationship between the rate of torque development hamstrings to quadriceps ratio and biomechanical parameters of hip and knee joints in the sagittal and frontal planes during the drop vertical jump test.Methods: Twenty healthy male recreational basketball players (aged 15-18) were recruited for this cross-sectional study. After measuring anthropometric data, the rate of torque development hamstrings to quadriceps ratio was assessed using an isokinetic Biodex system. Biomechanical variables were measured using a motion analysis system during the drop vertical jump test.Results: The rate of torque development hamstrings to quadriceps ratio (0-50 milliseconds) was negatively correlated with knee abduction angle (p = 0.028), knee adduction angle (p = 0.003), knee abduction moment (p = 0.023), and knee joint range of motion in the frontal plane (p = 0.01) during 17-50 ms after initial contact. Other biomechanical parameters did not significantly correlate with the rate of torque development hamstrings to quadriceps ratio.Conclusion: This study's results revealed that the torque development rate hamstrings to quadriceps ratio was negatively associated with knee kinematic and kinetic parameters. Based on the outcomes of this study and previous investigations, it can be acknowledged that the rate of torque development hamstrings to quadriceps ratio might be a useful tool to add to athlete injury screening.